As a Matter of Course - Call, Annie Payson, 1853-1940 (Salt Lake City, UT : Project Gutenberg, 2003)
"As a Matter of Course" by Annie Payson Call is a self-help book written during the late 19th century. The text aims to assist readers in identifying and removing various nervous irritants that contribute to physical disease and hinder personal fulfillment in daily life. It delves into the various pressures and expectations of modern civilization that can lead individuals to overlook the simplicity of maintaining a healthy and balanced life. The opening portion of the book begins with a metaphor of climbing a mountain, emphasizing the idea that many small irritants in everyday life can easily be overcome if faced with the right mindset. Call discusses how trivial problems often magnify our stress and nervousness, leading to mental and physical setbacks. She suggests that recognizing these issues and taking them as they come$1 (B"as a matter of course(3y$1 (Bcan help regain one$1 (Bs balance and peace of mind. The author further elaborates on how civilization$1 (Bs complexities contribute to chronic nervous irritation and proposes that a practical and non-sentimental approach to everyday challenges will lead to a healthier and more fulfilled life. (This is an automatically generated summary.)s
Introduction -- Physical care -- Amusements -- Brain impressions -- The triviality of trivialities -- Moods -- Tolerance -- Sympathy -- Others -- One's self -- Children -- Illness -- Sentiment versus sentimentality -- Problems -- Summary.
Release date is 2003-08-01
Produced by Steve Solomon
Keywords: Mental health -- Popular works